Experiential quality, experiential psychological states and experiential outcomes in an unmanned convenience store. (November 2019) - Wu, Hung-Che; Ai, Chi-Han; Cheng, Ching-Chan
Abstract: The objective of this study is to examine the experiential quality of consumers to better understand the relationship impact on their perceived experiential psychological states and experiential outcomes in the retail industry. The data were collected from 548 consumers who completed purchasing items at one Bingo Box in Shanghai, indicating that the proposed model fitted the data. Results will assist retail management in developing and implementing self-service strategies to increase experiential quality and experiential psychological states in order to increase consumer perceptions of experiential outcomes. Highlights: We examined how experiential quality influences experiential psychological states and experiential outcomes in the retail industry. We collected the data from a sample of 548 respondents who completed purchasing items at one BingoBox of Shanghai. The results assisted retail management in increasing experiential quality and experiential psychological states in order to promote perceptions of experiential outcomes.